Court, Kirk, and Community : Scotland 1470-1625 - Wormald, Jenny (New history of Scotland, 2018)
Charts the evolution of Scotland from a medieval and feudal to a modern, professional polity, and the transformation of its church and religious life from catholic to protestant.